Presence of the Cyanotoxin Microcystin in Arctic Lakes of Southwestern Greenland - Jessica V. Trout-Haney; Zachary T. Wood; Kathryn L. Cottingham (Toxins, 2016)
Cyanobacteria and their toxins have received significant attention in eutrophic temperate and tropical systems where conspicuous blooms of certain planktonic taxa release toxins into fresh water, threatening its potability and safe use for recreation. Although toxigenic cyanobacteria are not confined to high nutrient environments, bloom-forming species, or planktonic taxa, these other situations are studied les often studied. For example, toxin production in picoplankton and benthic cyanobacteria—the predominant photoautotrophs found in polar lakes—is poorly understood. We quantified the occurrence of microcystin (MC, a hepatotoxic cyanotoxin) across 18 Arctic lakes in southwestern Greenland. All of the focal lakes contained detectable levels of MC, with concentrations ranging from 5 ng·L−1 to >400 ng·L−1 during summer, 2013–2015. These concentrations are orders of magnitude lower than many eutrophic systems, yet the median lake MC concentration in Greenland (57 ng·L−1) was still 6.5 times higher than the median summer MC toxicity observed across 50 New Hampshire lakes between 1998 and 2008 (8.7 ng·L−1). The presence of cyanotoxins in these Greenlandic lakes demonstrates that high latitude lakes can support toxigenic cyanobacteria, and suggests that we may be underestimating the potential for these systems to develop high levels of cyanotoxins in the future.